A panel data analysis of economic growth determinants in 34 African countries - Larissa Batrancea; Malar Mozhi Rathnaswamy; Ioan Batrancea (Journal of Risk and Financial Management, 2021)
The research study investigated the economic determinants of economic growth in 34 countries across Africa during a two-decade period (2001-2019). For this purpose, the sample included a wide range of economies, from low income to high income and from low human development to high human development, according to recent international rankings provided by the World Bank and the United Nations Development Programme. By means of a multimodal approach centered on panel data modelling, we showed that economic growth, proxied by the GDP growth rate, was substantially influenced by economic indicators such as imports, exports, gross capital formation, and gross domestic savings. We also showed that foreign direct investment inflows and outflows play an important role for capital and savings. Our empirical results offer insights on strategies that national authorities could implement to boost economic growth and development across the African continent.
Keywords: 330; capital; exports; foreign direct investment; gross domestic product; import; savings